2/5 (-7) 5/2 as you know 2/5 x 5/2 = 1
so 1 x (-7) = -7
so the asnwer is -7
f(x) = 5x − 1 and g(x) = 2x^2 + 1
(f × g)(x) = (5x − 1)(2x^2 + 1)
(f × g)(x) = 10x^3 - 2x^2 + 5x - 1
Substitute x = - 3
(f × g)(-3) = 10(-3)^3 - 2(-3)^2 + 5(-3) - 1
(f × g)(-3) = 10(-27) - 2(9) -15 - 1
(f × g)(-3) =-270 - 18 - 16
(f × g)(-3) = -236
Answer
- 236
Answer:
-765
Step-by-step explanation:
-2-7 * 109
-2 - 763
-765
Answer:
x = 3/2
Step-by-step explanation:
We can use ratios to solve
6 6+x
-------- = -----------
4 5
Using cross products
6*5 = 4 * (6+x)
30 = 24 + 4x
Subtract 24 from each side
30 -24 = 24+4x-24
6 = 4x
Divide each side by 4
6/4 = 4x/4
3/2 = x